Accumulation of Autophagosomes in Semliki Forest Virus-Infected Cells Is Dependent on Expression of the Viral Glycoproteins - Eng, Kai Er (American Society for Microbiology, 2012)
Autophagy is a cellular process that sequesters cargo in double-membraned vesicles termed autophagosomes and delivers this cargo to lysosomes to be degraded. It is enhanced during nutrient starvation to increase the rate of amino acid turnover. Diverse roles for autophagy have been reported for viral infections, including the assembly of viral replication complexes on autophagic membranes and protection of host cells from cell death. Here, we show that autophagosomes accumulate in Semliki Forest virus (SFV)-infected cells. Despite this, disruption of autophagy had no effect on the viral replication rate or formation of viral replication complexes. Also, viral proteins rarely colocalized with autophagosome markers, suggesting that SFV did not utilize autophagic membranes for its replication. Further, we found that SFV infection, unlike nutrient starvation, did not inactivate the constitutive negative regulator of autophagosome formation, mammalian target of rapamycin, suggesting that SFV-dependent accumulation of autophagosomes was not a result of enhanced autophagosome formation. In starved cells, addition of NH(4)Cl, an inhibitor of lysosomal acidification, caused a dramatic accumulation of starvation-induced autophagosomes, while in SFV-infected cells, NH(4)Cl did not further increase levels of autophagosomes. These results suggest that accumulation of autophagosomes in SFV-infected cells is due to an inhibition of autophagosome degradation rather than enhanced rates of autophagosome formation. Finally, we show that the accumulation of autophagosomes in SFV-infected cells is dependent on the expression of the viral glycoprotein spike complex.